The death of authentic primitive art and other tales of progress - Errington, Shelly, 1944- (Berkeley : University of California Press, 1998)
Contents: ##Two centuries of progress ## The death of authentic primitive art ## Three ways to tell the history of (primitive) art ## What became authentic primitive art? ## The universality of art as a self-fulfilling prophecy ## The death of authentic primitive art ## Authenticity, primitivism, and art revisited ## And other tales of progress: nationalism, modernization, development ## Nationalizing the pre-Columbian past in Mexico and the United States ## The cosmic theme park of the Java
Includes bibliographical references (p. 285-300) and index.
boek